Design and Performance of a Single Axis Shake Table and a Laminar Soil Container - Alaie, Reza; Jamshidi Chenari, Reza (Civil Engineering Journal, 2018)
Correct evaluation of shear modulus and damping characteristics in soils under dynamic loading is one of the most important topics in geotechnical engineering. Shaking tables are used for physical modelling in earthquake geotechnical engineering and is key to the fundamental understanding and practical application of soil behaviour. The shaking table test is realistic and clear when the response of geotechnical problems such as liquefaction, post-earthquake settlement, foundation response and soil-structure interaction and lateral earth pressure problems, during an earthquake is discussed. This paper describes various components of the uniaxial shaking table at university of Guilan, Iran. Also, the construction of the laminar shear box is described. A laminar shear box is a flexible container that can be placed on a shaking table to simulate vertical shear-wave propagation during earthquakes through a soil layer of finite thickness. Typical model tests on sandy soil conducted on the shaking table and the results obtained are also presented. Appropriate evaluation of shear modulus and damping characteristics of soils subjected to dynamic loading is key to accurate seismic response analysis and soil modelling programs. The estimated modulus reduction and damping ratio were compared to with Seed and Idrissâs benchmark curves.